University students’ self-efficacy: A contributing factor in TOEFL performance - Marisa Yoestara; Zaiyana Putri (Studies in English Language and Education, 2019)
Self-efficacy is one of the often-underestimated factors, which in fact, has an influence in determining human action. This study aims to find out the correlation between self-efficacy and the TOEFL performance of the students in two universities in Banda Aceh, namely Syiah Kuala University and Serambi Mekkah University. This study employed the correlational design to find out the correlation between the two main variables (self-efficacy and TOEFL performance). The sampling technique used in this study was the stratified sampling method with a total sample of 200 university students, both English, and Non-English majors. Furthermore, to collect the data, two instruments were used, namely the self-efficacy questionnaire and the TOEFL test. In analyzing the data, Pearson’s Correlation was used to find out the correlation. The result shows that there is a positive and low correlation between university students’ self-efficacy and their TOEFL performance (r=.249). Despite the correlation is low, self-efficacy is still considered to contribute to the TOEFL score. Therefore, it is suggested that TOEFL instructors consider the variable of self-efficacy in their teaching. Furthermore, it is expected that future research continues this study by enlarging the sample size in different levels of education and in different areas.